Case Report: Diagnosis of Myelodysplastic Syndrome in a 72-Year-Old Female With Interstitial Lung Disease - Bizymi, Nikoleta; Pitsidianakis, Georgios; Ierodiakonou, Despo; Stathakis, Georgios; Vasarmidi, Eirini; Hiraki, Stavroti; Bolaki, Maria; Karagiannis, Konstantinos; Fanaridis, Michail; Liopyrakis, Konstantinos; Marinos, Leonidas; Xilouri, Irini; et al. (Frontiers in Medicine, 2021)
Acute fibrinous and organizing pneumonia (AFOP) is an entity that can be secondary to various conditions leading to lung injury such as infections, malignancies and various auto-immune conditions or idiopathic interstitial lung disease when no obvious underlying cause is identified. Myelodysplastic Syndromes (MDS), on the other hand, are a spectrum of clonal myeloid disorders, with a higher risk of acute leukemia, characterized by ineffective bone marrow (BM) hematopoiesis and thus peripheral blood (PB) cytopenias. Immune deregulation is thought to take part in the pathophysiology of the disease, including abnormal T- and/or B-cell responses, innate immunity and cytokine expression. In the literature there are a few case reports of patients with MDS that have presented pulmonary infiltrates and were diagnosed as AFOP or organizing pneumonia (OP). It is rare, though, to have isolated pulmonary infiltrates without Sweet’s syndrome or even pulmonary infiltrates to precede the diagnosis and the treatment of MDS, which was our case. We present a 72-year-old female developing new lung infiltrates refractory to antibiotic treatment that responded well to corticosteroids and was histologically described as OP. The treatment was gradually successfully switched to mycophenolate mofetil (MMF). The patient was later diagnosed with MDS. This interesting case report suggests firstly that a diagnosis of AFOP or OP should alert the clinician to search an underlying cause including MDS and vice versa, the use of systemic steroids should not be postponed, and finally MMF can successfully be used in these patients.